Sociohistory of sport and physical practices in Gabon from independence to the present day. - (:unkn) unknown (My University, 2016)
The introduction of western institutional system in black francophone Africa, with the effect the arrival of new physical practices resulted in African societies of a destabilization of traditional practices. Analyses show in particular that African will start in organizing distant practices of their cultural realities. In Gabon, the colonial system introduced the practice of modern sports in the late XIXth century and organizes the teaching of PE from 1925 with the creation of a committee of physical education and military training. Traditional body practice will thus be competing with modern sports and losing their prominent status. Facing this situation, many questions structure our research: Have the Gabonese assimilate sports and modern western cultural body practices, with which playors and which institutions? Does a reappropriation process implement at the time of accession to independence? What place endued traditional practices? What conclusion can we draw from these years of initiation and practice in sport and body activities? To study this process of diffusion of sport and the terms of acculturation in Gabon, our search is based on a socio-historical approach supported by an analysis of the C.N.A.O.M archives and those of Gabon, and a series of interviews with the players of Gabonese society which may inform about the sport and traditional practices in this country.Keywords: Traditional practices, Sport, Culture, Acculturation, Gabon.
Keywords: African Research